Global DNA methylation (LINE-1) associated with exposure to arsenic-contaminated environment and with type of arsenical skin lesions in Thailand. Issue 3 (3rd April 2019) - Phetliap, Witchaya; Geater, Alan; Rozek, Laura S.; Oshikawa, Shoko; Helmick, Katherine; Rentschler, Katie; Kojo, Yasuko; Thaicharoen, Siriluck
ABSTRACT: The effects of chronic arsenic exposure mode on DNA methylation and skin lesion type are unclear. These relationships were investigated in an arsenic-contaminated area of southern Thailand. Cases with arsenical skin lesions (n = 131) and lesion-free controls (n = 163) were selected from an arsenic-contaminated sub-district, as well as 105 controls from a non-contaminated area. Type and severity of skin lesions and salivary global DNA methylation (LINE-1) were determined. Arsenic exposure was characterized as occupational, domestic and current (toe-nail arsenic). Associations were explored using logistic regression. Cases and controls had lower LINE-1 methylation and higher toenail arsenic than external controls (74.65% and 74.61% vs 76.05%, p < 0.001 for each). Cases were more likely to have been exposed domestically (ORtotal 1.76, 95% ci 1.00, 3.11; and 2.22, 95% ci 1.22, 4.03; Ptrend = 0.005 for exposure <36 and ≥36 years). More severe spotty hyperpigmentation was related to higher LINE-1 methylation (Ptrend =0.006). LINE-1 methylation was positively associated with toenail arsenic only among non-symptomatic exposed subjects (OR 1.31, 95% ci 1.06, 1.64; p = 0.014). Exposure to an arsenic-contaminated environment results in global DNA hypomethylation. However, among symptomatic subjects, increased global DNA methylation was associated with increased severity of spotty hyperpigmentation.